The Renewal of the Twenty Years in Theater: Revisions Based on The Danton Case by Stanisława Przybyszewska from 2008 - Katarzyna Fazan (Postscriptum Polonistyczne)
The article results from the author’s participation in a project proposing interdisciplinary perspectives on contemporary revisions of the interwar period (1918–1939), including the interwar period in theater. The change in the way of interpreting the culture of this period was presented by the author using the examples of two 2008 productions of Stanisława Przybyszewska’s Danton’s Case, staged by important directors active after 1989: Jan Klata (Teatr Współczesny in Wrocław) and Paweł Łysak (Teatr Polski in Bydgoszcz). This makes it possible to bring to the fore not the monumental theater of Leon Schiller, built on Polish Romanticism as a continuation of the freedom tradition, but on a program of rejected – both in the 1930s and during the communist period – leftist ideas, important for socio-cultural progress. The mentioned stage production of the twenty-first century draw attention to the current of aesthetic-political engagement in Polish interwar theater, and inscribe this theme in the program of dismantling earlier theatrical hierarchies built on the concept of a national community united by Romantic myth. Despite the fact that Stanisława Przybyszewska was not part of the feminist movement, the renewal of the meanings and form of her drama can be linked today, firstly, to the appreciation of her as an important voice of a politically and socially conscious author, proposing Brechtian-style theater, and secondly, to the revision of the twentieth century seen anew as a moment of women’s attempt at breaking the masculocentric order of social life.